Perbedaan Tingkat Kecanduan Game Online Antara Siswa Laki-laki dan Perempuan di SMA Negeri 6 Padang - Suci Aulya; Linda Fitria; Yuliawati Yunus (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2024)
This study aims to determine the differences in the level of online game addiction between male and female students at SMA Negeri 6 Padang. The type of research used in this study is quantitative with a comparative type. The study population consisted of people registered in the 2024/2025 academic year, with a sample of 118 people taken using purposive sampling techniques. This study examines the differences in the Level of Online Game Addiction Between Male and Female Students at SMA Negeri 6 Padang. The instrument used for data collection in this study was a questionnaire compiled according to the Likert model. Data analysis was carried out using statistical programs on SPSS 24.0 and Microsoft Excel computers. Based on the results of the t-test, it is known that the significance value of 2-sided equal variances assumed is less than 0.05, which is 0.045 <0.05. So, it can be concluded that there is a no significant difference in the level of online game addiction between male and female students at SMA Negeri 6 Padang. Some positive impacts such as increased cognitive skills, development of creativity, and business and industry opportunities and negative impacts such as addiction to mental health problems, adolescent behavioral disorders, and the spread of negative information and violence. Symptoms of students who are addicted to online games are spending more time playing online games, often falling asleep at school, often neglecting assignments, school grades that are starting to decline and preferring to play online games rather than playing with friends.